M. I. Wallace, Finding God in the Singing River. Christianity, Spirit, Nature, Minneapolis, Augsburg Fortress, 2005, 183 pp. - Paz, Patricia (2007)
Fil: Paz, Patricia. Investigadora independiente; Argentina